Assessing the Cumulative Impacts of Forest Management on Forest Age Structure Development and Woodland Caribou Habitat in Boreal Landscapes: A Case Study from Two Canadian Provinces - Mackey, Brendan; Campbell, Carly; Norman, Patrick; Hugh, Sonia; DellaSala, Dominick A; Malcolm, Jay R; Desrochers, Mélanie; Drapeau, Pierre (Land, 2023)
The Canadian boreal forest biome has been subjected to a long history of management for wood production. Here, we examined the cumulative impacts of logging on older forests in terms of area, distribution and patch configuration in the managed forest zones of the Eastern Canadian provinces of Ontario and Quebec. We also examined the consequences of these cumulative impacts on a once widely distributed and now threatened species, the woodland caribou (Rangifer tarandus caribou). The cumulative area of recently logged forest (since ~1976) was 14,024,619 ha, with 8,210,617 ha in Quebec and 5,814,002 ha in Ontario. The total area of older forest was 22,672,369 ha, with 12,390,740 ha in Quebec and 10,281,628 ha in Ontario. Patch statistics revealed that there were 1,085,822 older forests with core patches < 0.25 ha and an additional 603,052 < 1.0 ha. There were 52 > 10,00–50,000 ha and 8 < 50,000 ha. Older forest patches (critical caribou habitat) in the 21 local population ranges totalled 6,103,534 ha, distributed among ~387,102 patches with 362,933 < 10 ha and 14 > 50,000 ha. The median percentage of local population ranges that was disturbed was 53.5%, with Charlevoix having the maximum (90.3%) and Basse Côte-Nord the least (34.9%). Woodland caribou local population ranges with disturbed suitable habitats >35% are considered unable to support self-sustaining populations. We found that for the 21 caribou local population ranges examined, 3 were at very high risk (>75% area disturbed), 16 at high risk (>45 ≤ 75% area disturbed), and 2 at low risk (≤35% area disturbed). Major changes are needed in boreal forest management in Ontario and Quebec for it to be ecologically sustainable, including a greater emphasis on protection and restoration for older forests, and to lower the risks for caribou populations. Full Text